2013
DOI: 10.1002/iub.1218
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of phospholipase C-β1GTPase-activating protein (GAP) function and relationship to Gqefficacy

Abstract: How cells regulate G q efficacy (initiation and termination of G q signaling) to effect response remains a central question in pharmacology and drug discovery. Phospholipase C-b 1 (PLCb 1 ) is an effector and a GTPase activating protein (GAP) specific to Ga q . The physiological function of PLC-b 1 GAP remains unclear and controversial. GAPs are generally thought to function in deactivation of G q signaling. However, PLC-b 1 GAP has also been shown to increase signaling efficiency through kinetic coupling with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…It would be surprising to see any activity of Gαq GTP –PLCβ, if PLCβ could induce 1000-fold higher hydrolysis of GTP on Gαq in cells, as seen in vitro ( 2 , 10 , 24 , 25 , 58 , 59 , 60 ). In cells, the activated GPCRs are proposed to suppress the GAP activity of PLCβ mentioned above ( 24 ). Also, it was suggested that the enhanced GEF activity of GPCR (to activate the heterotrimer) in cells outcompete PLCβ–GAP activity ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It would be surprising to see any activity of Gαq GTP –PLCβ, if PLCβ could induce 1000-fold higher hydrolysis of GTP on Gαq in cells, as seen in vitro ( 2 , 10 , 24 , 25 , 58 , 59 , 60 ). In cells, the activated GPCRs are proposed to suppress the GAP activity of PLCβ mentioned above ( 24 ). Also, it was suggested that the enhanced GEF activity of GPCR (to activate the heterotrimer) in cells outcompete PLCβ–GAP activity ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, it was suggested that the enhanced GEF activity of GPCR (to activate the heterotrimer) in cells outcompete PLCβ–GAP activity ( 23 ). It was also predicted that PLCβ GAP activity does not downregulate Gαq GTP -induced PLC activation but enhances it ( 24 ). These theories collectively suggest that the GAP activity of PLCβ behaves differently in living cells compared with its demonstrated efficacy in vitro .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation